2006
DOI: 10.1124/jpet.106.109363
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibition of Arterial Smooth Muscle Tonic Contractions by the Selective Myosin II Inhibitor, Blebbistatin

Abstract: Blebbistatin is reported to be a selective and specific small molecule inhibitor of the myosin II isoforms expressed by striated muscles and nonmuscle (IC 50 ϭ 0.5-5 M) but is a poor inhibitor of purified turkey smooth muscle myosin II (IC 50 ϳ80 M). We found that blebbistatin potently (IC 50 ϳ3 M) inhibited the actomyosin ATPase activities of expressed "slow" [smooth muscle myosin IIA (SMA)] and "fast" [smooth muscle myosin IIB (SMB)] smooth muscle myosin II heavy-chain isoforms. Blebbistatin also inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
79
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 41 publications
12
79
1
1
Order By: Relevance
“…Blebbistatin inhibited the activities of unphosphorylated (IC 50 ϭ 17.5 Ϯ 0.7 and 10.1 Ϯ 0.7 M for gizzard and bovine smooth muscle myosin II, respectively) and phosphorylated (IC 50 ϭ 23.5 Ϯ 2.8 M for gizzard smooth muscle myosin II) forms of myosin II. These results suggest that blebbistatin inhibits the activity of smooth muscle myosin II at lower concentrations than previously reported (27) and agrees with the result of Eddinger et al (7).…”
Section: Dissociation Of Smooth Muscle Myosin II From Actin Filamentssupporting
confidence: 93%
See 2 more Smart Citations
“…Blebbistatin inhibited the activities of unphosphorylated (IC 50 ϭ 17.5 Ϯ 0.7 and 10.1 Ϯ 0.7 M for gizzard and bovine smooth muscle myosin II, respectively) and phosphorylated (IC 50 ϭ 23.5 Ϯ 2.8 M for gizzard smooth muscle myosin II) forms of myosin II. These results suggest that blebbistatin inhibits the activity of smooth muscle myosin II at lower concentrations than previously reported (27) and agrees with the result of Eddinger et al (7).…”
Section: Dissociation Of Smooth Muscle Myosin II From Actin Filamentssupporting
confidence: 93%
“…Eddinger et al (7) recently reported that the ATPase activity of smooth muscle myosin was inhibited by blebbistatin at a concentration low enough to explain our data (15) and aroused our interest in the effect of blebbistatin on the migration of vascular smooth muscle cells (VSMCs). In the present study, we analyzed the mechanism of inhibition of blebbistatin on VSMC migration on the basis of the motor activity of smooth muscle myosin II.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…In vitro biochemical studies have shown that blebbistatin is less effective on turkey smooth muscle myosin than it is on cytoplasmic myosin (40). Moreover, there is evidence that treatment with 10 -30 M blebbistatin effectively inhibits the contraction of smooth muscle tissues (41,42). Therefore, it is likely that actin polymerization, not tension, is necessary for the translocation of ␤-catenin and the recruitment of ␤-catenin to N-cadherin.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Blebbistatin stabilizes the ADP-P i complex of the S1 myosin head that precedes the tension-generating step catalyzed by release of P i , thus inhibiting myosin from entering into the cross-bridge cycle (24). Blebbistatin inhibits mammalian smooth muscle tension and actomyosin ATPase activity (9), does not inhibit myosin light chain phosphorylation in smooth or striated muscle (9,49), and because it has no effect on action potentials or Ca 2ϩ mobilization, it can selectively uncouple excitation-contraction coupling in cardiac muscle (11).…”
mentioning
confidence: 99%